DEVELOPMENT OF HOLISTIC COUNTING BOX LEARNING MEDIA TO IMPROVE STUDENTS' COGNITIVE ABILITIES IN MATHEMATICS SUBJECTS - Agustin, Nurhaningtyas; Pradana, Akhmad Aji; Mubaidilla, Irfa'i Alfian; Suswatiningsih (Joyful Learning Journal, 2025)
The problem that is the background to this research is that there are students who still have difficulties learning mathematics. Apart from the high level of difficulty in learning mathematics, the teacher's method of delivery, which is considered monotonous, also makes students lazy about learning mathematics and results in most of them having low grades in this subject. This research is to see the validity of developing holistic counting box learning media to improve students' cognitive abilities. (2) To produce practical development of holistic counting box learning media to improve students' cognitive abilities. (3) To produce effective development of holistic counting box learning media to improve students' cognitive abilities. This research uses the Research and Development (R&D) method, which uses the 4-D development model. The 4-D development model includes 4 stages, namely definition, planning or design, development, and dissemination. Based on the validity test, the media meets the very valid category. Validation of the appropriateness of media expert data received a score of 96%. Validation of material expert eligibility with a score percentage of 97.5%. The level of practicality of the media obtained results with a percentage of 91%, the teacher's response to the media developed by the researcher with a percentage result of 95.5%, and the response of students to the media developed by the researcher with a percentage result of 97%, with each questionnaire result in very high criteria. Good. Student learning outcomes increased after being calculated using the gain normality test, with an average pretest score of 62.5 while the average posttest score was 89 and the average gain normality test calculation was 0.75 in the high category. The results of this research and development can be concluded that the holistic mathematics counting box learning medium is included in the valid, practical, and effective category for use in mathematics learning to improve students' cognitive abilities.